La derecha peronista en perspectiva - Juan Luis Besoky (Centre de Recherches sur les Mondes Américains, 2013)
In this paper I analyze the relevance of the term "Peronist right" to refer to organizations that claiming allegiance to Juan Domingo Peron and Maria Estela Martinez de Peron, politically and ideologically confronted the revolutionary tendency of Peronism and the left wing. Those organizations are: the Juventud Peronista de la República Argentina, the Juventud Sindical Peronista, the Comando de Organización, the Alianza Libertadora Nacionalista and the Concentración Nacional Universitaria, among others. To this critically I analyze how the general literature on the period has called to these organizations: in some cases as part of nationalism, in other directly as members of the repressive state and often as Orthodox sectors of Peronism or simply "from right". All these names are considered for propose rescue “Peronist right” as a category of analysis, based on some common denominators such as nationalism, historical revisionism, and anti-Semitism, and in certain shared cultural traits that allow the formation of an orthodox Peronist in the second half of the twentieth century.